The genetic-associated analysis of g. 22 G>C single-nucleotide polymorphism in F cathepsin gene of different pig breeds - Балацький, В. М.; Вовк, В. О.; Буслик, Т. В.; Ільченко, М. О.; Олійниченко, Є. К. (Scientific Progress & Innovations, 2018)
Lately, stud pig breeding has increasingly been getting based on the use of marker-associated selection (MAS) technology, which involves the genotyping of individuals according to the loci controlling economic characteristics and the use of the received molecular information for evaluating the genotypes of diferentt animal selection. A large number of candidate genes belonging to such loci (QTL – quantitative traits loci) that influence the reproductive, fattening and meat quality parameters of pigs have been established. But not so many genes and the corresponding DNA markers, which in terms of their informativity and the strength of association with the traits, can be effectively used in practical selection. The selection in pig breeding involves a set of measures that ensure the development of animal productivity improving the animal, herds and breeds. Effective breeding is not possible without involving new approaches that predict animal DNA genotyping by the chosen polymorhisms. Cathepsine F (CTSF) is the potential candidate for marker-assosiated selection, which directly participates in fat storing processes and meat qualities of pigs. The genetic structure of such pig breeds as Ukrainian Large White, Poltava Meaty, Ukrainian Large Black and Mirgorods’ka for cathepsin F gene (CTSF g.22 G> C SNP) was determined, and basic population parameters were established. In all populations, the genetic marker was characterized by polymorphism with the predominance of the g.22C allele frequency. The level of informativity of CTSF g.22 G> C SNP was found at the optimal level for associative analysis (PIC=0.358–0.375), which allows to search for marker associations with traits of pig productivity in the studied subspecies. In the subpopulation of Ukrainian Large White breed, the analysis of the genetic marker CTSF g.22 G> C SNP was studied by the following traits: the age for reaching the live weight of 100 kg, the thickness of the backfat at the level of the 6th–7th rib, 10th ribs, in the sacrum area and the average daily weight gain. After the statistical analysis the tendency towards the association of the CTSF g.22 G> C genetic marker with the age parameter for reaching the live weight of 100 kg (p=0.07) was found. The other studied populations of pig breeds can further be used for associative researches in order to find assosiations between the chosen genetical marker and meat and backfat quality parameters.